Complications during Vaginal Sacrospinous Fixation along with McCall Culdoplasty in Stage III and IV POP - Begum, Bilkis; Begum, Bilkis; Begum, Rowshan Ara (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
In Bangladesh, about half a million women are suffering from stage III or IV pelvic organ prolapse (POP). With traditional surgical methods, there is a chance of recurrence, especially of apical prolapse. Sacrospinous fixation (SSF) along with MacCall Culdoplasty during vaginal hysterectomy can reduce this recurrence rate enormously. This study was designed to identify, manage as well as to prevent per-/post-operative complications during SSF. The study period was from August 2017 to December 2021 at Kumudini Women’s Medical College and Hospital, Bangladesh. Total 335 stage III and IV utero-vaginal prolapse cases were included in this study. The surgeries performed were vaginal hysterectomy followed by modified McCall Culdoplasty and right-sided vaginal sacrospinous ligament fixation (SSF) along with anterior and posterior fascial closure and perineorrhaphy. A standard data collection sheet was used to record the information. Per-operatively, main complications were hemorrhage (3.57%) due to vessel injury and rectal injury (0.90%). The immediate early postoperative complication was buttock pain (24%). Of these, in 97.53% cases, pain subsided within 6 weeks with analgesic and counselling. Only one patient had recurrence of apical prolapse within 1st week of operation. It should be concluded that with proper knowledge of anatomy and careful surgical technique, most of the complications can be avoided. Bangladesh J Obstet Gynaecol, 2022; Vol. 37(2): 90-97